Symbiosis Evolution of E-commerce Platform Ecosystem with Cooperative and Competitive Effect: An Extended Population Density Logistic Model-Based Simulation. (29th March 2023) - Du, Shan
Abstract : With the development of the Internet, traditional platforms have been challenged by competition from participants on the platform. However, it is unclear how these two types of population, which are in competition but also mutually dependent, can co-exist in the new platform ecosystem. This paper sheds light on that key phenomenon by extending the population density logistic model of the e-commerce platform ecosystem between participants and platforms based on the symbiosis theory. By solving the logistic equation, we acquire the evolutionary trajectory and final size of populations under different symbiotic patterns. The results reveal that the cooperative and competitive effect determines the equilibrium outcome of the symbiosis evolution of e-commerce platform ecosystem. In the asymmetric symbiosis mode, only one population is influenced by positive synergy that increases population density and promote evolution. The contribution coefficient of subordinate to the dominant is greater than the feedback coefficient from the dominant; the trends of output value are inconsistent. The symmetric symbiosis mode is the optimal model for participants and platforms. The effect "1 + 1 > 2 " can only be achieved under the symmetric symbiosis mode, and the growth of the participants and the platforms is more stable and sufficient than that in other modes. The findings will provide additional perspectives to promote the sustainable development of e-commerce platform ecosystem considering the cooperative and competitive effect.